Heat transfer measurement techniques in microchannels for single and two-phase Taylor flow. (5th November 2019) - Abdollahi, Ayoub; Norris, S.E.; Sharma, Rajnish N.
Highlights: Heat transfer measurement techniques in microchannel are presented. Major source of experimental error in estimation of Nusselt number is explained. Heat transfer of single phase flow in a square microchannel is studied. Nusselt number measured for Reynolds numbers ranging from 20 to 100. Abstract: Accurate measurement of heat transfer in experiments of single, two-phase liquid-liquid and gas-liquid Taylor flows without phase change in microchannels is a challenging task. In this paper we review experimental studies of these flows, and the methods of heat transfer measurement used, in order to gain insight into the effect of some critical dimensionless groups on the accuracy of the estimates of the heat transfer. It was found that experimental measurements of Nusselt number often disagree with theoretical predictions, particularly at low Reynolds numbers. We identify the major causes of error in experimental estimation of the Nusselt number, and propose solutions to decrease the error in experimental heat transfer measurement. Measurements obtained from a new microchannel experimental setup are reported upon, to demonstrate these sources of error.